(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2022)
This paper presents a literature review of studies that analyze the production regarding large-scale assessment policies and, more specifically, the large-scale assessment of literacy. In all, 16 studies were found between 2012 and 2021, two of which specifically addressed large-scale literacy assessment. It was concluded that few works still focus on meta-research on large-scale assessment and large-scale assessment policies aimed at literacy, indicating the possibility of further studies on the subject and its theoretical-epistemological issues. Keywords: Education Policy. Meta-research. Large-scale assessment. Literacy.